Twenty-first aminoacyl-tRNA synthetase–suppressor tRNA pairs for possible use in site-specific incorporation of amino acid analogues into proteins in eukaryotes and in eubacteria - Kowal, Anne K. (The National Academy of Sciences, 2001)
Two critical requirements for developing methods for the site-specific incorporation of amino acid analogues into proteins in vivo are (i) a suppressor tRNA that is not aminoacylated by any of the endogenous aminoacyl-tRNA synthetases (aaRSs) and (ii) an aminoacyl-tRNA synthetase that aminoacylates the suppressor tRNA but no other tRNA in the cell. Here we describe two such aaRS–suppressor tRNA pairs, one for use in the yeast Saccharomyces cerevisiae and another for use in Escherichia coli. The “21st synthetase–tRNA pairs” include E. coli glutaminyl-tRNA synthetase (GlnRS) along with an amber suppressor derived from human initiator tRNA, for use in yeast, and mutants of the yeast tyrosyl-tRNA synthetase (TyrRS) along with an amber suppressor derived from E. coli initiator tRNA, for use in E. coli. The suppressor tRNAs are aminoacylated in vivo only in the presence of the heterologous aaRSs, and the aminoacylated tRNAs function efficiently in suppression of amber codons. Plasmids carrying the E. coli GlnRS gene can be stably maintained in yeast. However, plasmids carrying the yeast TyrRS gene could not be stably maintained in E. coli. This lack of stability is most likely due to the fact that the wild-type yeast TyrRS misaminoacylates the E. coli proline tRNA. By using error-prone PCR, we have isolated and characterized three mutants of yeast TyrRS, which can be stably expressed in E. coli. These mutants still aminoacylate the suppressor tRNA essentially quantitatively in vivo but show increased discrimination in vitro for the suppressor tRNA over the E. coli proline tRNA by factors of 2.2- to 6.8-fold.